Advanced hemodynamic monitoring before and after transjugular intrahepatic portosystemic shunt: implications for selection of patients - a prospective study - Saugel, Bernd; Gaa, Jochen; Berger, Hermann (Radiology, 2012)
PurposeTo investigate immediate and short-term effects of transjugular intrahepatic portosystemic shunt (TIPS) on cardiocirculatory, hepatic, and renal function and characterize predictors for TIPS outcome in terms of organ function after TIPS.Materials and MethodsThis prospective study was approved by the ethics committee at a university hospital and was conducted in a medical intensive care unit. Informed consent was obtained. Twenty patients with indication for TIPS were enrolled. Monitoring of hemodynamic and hepatic function (transpulmonary thermodilution, indocyanine green plasma disappearance rate [ICG-PDR]) was performed. Biochemical markers of organ function were obtained. Statistical analysis (Wilcoxon test, Spearman correlation, multivariate linear regression analysis, receiver operating characteristic [ROC] analysis) was performed.ResultsAfter TIPS, central venous pressure (median, 11 vs 15 cm H2O; P < .001), cardiac index (3.4 vs 3.8 L/min/m2; P = .001), and global end-diastolic volume index (GEDVI) (726 vs 775 mL/m2; P = .003) increased significantly. Portosystemic pressure gradient (28 vs 11 cm H2O; P < .001) and systemic vascular resistance index (1610 vs 1384 dyn · sec · cm−5 · m2; P = .015) decreased significantly. Creatinine (1.1 vs 1.1 mg/dL; P = .008) and blood urea nitrogen (BUN) (27 vs 21 mg/dL; P = .006) decreased significantly. Bilirubin (1.8 vs 2.2 mg/dL; P = .032) and international normalized ratio (1.4 vs 1.5; P = .022) increased significantly. ICG-PDR significantly deteriorated after TIPS (P = .006). Higher baseline creatinine was independently associated with a decrease in creatinine after TIPS (R = 0.816, P < .001). ROC analysis identified baseline BUN (P = .026, area under ROC curve [AUC] = 0.818), cystatin C (P = .033, AUC = 0.805), and creatinine (P = .052, AUC = 0.779) as predictors of a decrease in creatinine of 0.5 mg/dL or greater and/or 25% or greater. An increase in bilirubin of 1 mg/dL or greater 1 week after TIPS was significantly associated with high baseline BUN (P = .007, AUC = 0.893) and high central venous pressure (P = .040, AUC = 0.800). Lower baseline alanine aminotransferase (P = .002, AUC = 1.000) and cardiac power index · GEDVI (P = .005, AUC = 0.960) predicted favorable TIPS outcome (creatinine decrease of ≥0.2 mg/dL without model for end-stage liver disease score increase of more than one point).ConclusionPatients with renal insufficiency, compensated hepatocellular function, decreased cardiac preload, and decreased cardiac performance benefit most from TIPS.© RSNA, 2011Supplemental material: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.11110043/-/DC1
Published online:Jan 1 2012
Gesehen am 25.06.2018